Oral Administration of Lactococcus lactis Producing Interferon Type II, Enhances the Immune Response Against Bacterial Pathogens in Rainbow Trout - Santibañez, Alvaro; Paine, Diego; Parra, Mick; Muñoz, Carlos; Valdes, Natalia; Zapata, Claudia; Vargas, Rodrigo; Gonzalez, Alex; Tello, Mario (Frontiers in Immunology, 2021)
Lactic acid bacteria are a powerful vehicle for releasing of cytokines and immunostimulant peptides at the gastrointestinal level after oral administration. However, its therapeutic application against pathogens that affect Rainbow trout and Atlantic Salmon has been little explored. Type II interferon in Atlantic Salmon activates the antiviral response, protecting against viral infections, but its role against bacterial infections has not been tested in vivo. In this work, through the design of a recombinant lactic acid bacterium capable of producing Interferon gamma from Atlantic salmon, we explore its role against bacterial infections and the ability to stimulate systemic immune response after oral administration of the recombinant probiotic. Recombinant interferon was active in vitro, mainly stimulating IL-6 expression in SHK-1 cells. In vivo, oral administration of the recombinant probiotic produced an increase in IL-6, IFN and IL-12 in the spleen and kidney, in addition to stimulating the activity of lysozyme in serum. The challenge trials indicated that the administration of the IFN-producing probiotic doubles the survival in fish infected with F. psychrophilum. In conclusion, our results show that the oral administration of lactic acid bacteria producing IFN manages to stimulate the immune response at a systemic level, conferring protection against pathogens, showing a biotechnological potential for its application in aquaculture.